Sol-gel spin coating growth of gallium nitride thin films : a simple, safe, and cheap approach - Fong, Chee Yong; Ng, Sha Shiong (Penerbit Universiti Sains Malaysia, 2018)
Wide direct band gap gallium nitride (GaN) semiconductor has received significant attention as an ideal material for various applications in the optoelectronic devices. One major use of GaN is the development of energy-efficient solid state light-emitting diodes. Currently, most commercially available GaN semiconductor are produced through advanced deposition techniques which involve sophisticated technologies and are relatively expensive and complicated to setup. As an alternative, the sol-gel spin coating method, which is relatively simpler, cheaper, safer, and more scalable was proposed. In this book, the process route and recipe for producing highly c-oriented crystalline GaN thin films via the sol-gel spin coating approach were described in detail. Some insights into the factors affecting the surface morphology as well as structural and optical properties of the deposited films were presented. Eventually, this book could inspire further studies into the development of low-cost GaN thin films.
Keywords: Semiconductors.; Gallium nitride.; Thin films.; elektronické knihy; electronic books